2017
DOI: 10.1002/ange.201705734
|View full text |Cite
|
Sign up to set email alerts
|

TMSCF3 as a Convenient Source of CF2=CF2 for Pentafluoroethylation, (Aryloxy)tetrafluoroethylation, and Tetrafluoroethylation

Abstract: An ew method for the on-site preparation of tetrafluoroethylene (TFE) and ap rocedure for its efficient use in pentafluoroethylation by fluoride addition were developed by using as imple two-chamber system. The on-site preparation of TFE was accomplished by dimerization of difluorocarbene derived from (trifluoromethyl)trimethylsilane (TMSCF 3 )u nder mild conditions.O ther fluoroalkylation reactions,s uch as (aryloxy)tetrafluoroethylation and tetrafluoroethylation processes,w ere also achieved using as imilar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 71 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…[20] In the crystal lattice, the Y-shaped coordination geometry of 2,w hich manifests in an N-Cu-N bond angle of 80.79(8)8,i sc onsiderably distorted, which is also reflectedi nt he C-Cu-N bond angles [147.28(10)8/131.64(10)8]a nd the CuÀNd istances [2.101(2) / 2.013(4) ], whereas the degree of distortion in 2 is slightly smaller than that observed in (bpy)CuC 2 F 5 (bpy = 2,2'-bipyridyl). [4h] In agreement with the report by Hu, [11] treatment of 2 with iodobenzene (3a)i nD MF at 60 8Cy ieldedp entafluoroethylbenzene (4a)i n8 5% yield (Scheme 2). In response to the result of the stoichiometricr eaction, our subsequent efforts were devoted to the development of aC u I -catalyzed pentafluoroethylation of iodoarenes in the presence of metal fluoride as as ource of fluoridea nions.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…[20] In the crystal lattice, the Y-shaped coordination geometry of 2,w hich manifests in an N-Cu-N bond angle of 80.79(8)8,i sc onsiderably distorted, which is also reflectedi nt he C-Cu-N bond angles [147.28(10)8/131.64(10)8]a nd the CuÀNd istances [2.101(2) / 2.013(4) ], whereas the degree of distortion in 2 is slightly smaller than that observed in (bpy)CuC 2 F 5 (bpy = 2,2'-bipyridyl). [4h] In agreement with the report by Hu, [11] treatment of 2 with iodobenzene (3a)i nD MF at 60 8Cy ieldedp entafluoroethylbenzene (4a)i n8 5% yield (Scheme 2). In response to the result of the stoichiometricr eaction, our subsequent efforts were devoted to the development of aC u I -catalyzed pentafluoroethylation of iodoarenes in the presence of metal fluoride as as ource of fluoridea nions.…”
supporting
confidence: 87%
“…[10b] After our manuscript on this oxycupration chemistry was published online, we noted that, during roughly thes ame period,H ua nd co-workers had developed related( aryloxy)tetrafluoroethylation and pentafluoroethylation reactions, in which TFE was prepared in situf rom CF 3 SiMe 3 . [11] Although they demonstrated the related syntheticu tility of pentafluoroethylations employing TFE, special efforts to distinguish two possible routes to the key CuÀC 2 F 5 intermediates, that is, the fluorocupration of TFE [12,13] or the transmetalation between CsC 2 F 5 and copper(I) halide, [3b, 14] were not undertaken. In addition, applicationso ft hese Cu-catalyzed pentafluoroethylations were not carried out.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[22b,d] While literature precedents on the Wittig gem-difluoroalkenylation employed high reaction temperatures, [22c-e] we postulated that the enhanced heat transfer might also accelerate the dissociation of the ylide as well as dimerization of difluorocarbene to form tetrafluoroethylene. [23] We found that a decrease in temperature improved the reaction yields with 0 8C being the optimal (Table 1, entry 1-5). This is presumably due to the stabilization of the transient ylide.…”
Section: Resultsmentioning
confidence: 84%
“…[5] Most of the current methods for the syntheses of pentafluoroethylated aromatic compounds use ac ertain C 2 F 5 source,b ut these reactions suffer from the following drawbacks:1 )not readily available,e xpensive or hard to handle C 2 F 5 sources;2 )harsh reaction conditions;3 )potentially explosive gaseous intermediate,a nd/or 4) low yields. [6][7][8][9][10][11][12] Owing to these problems,a ne fficient method for the synthesis of aromatic pentafluoroethyl compounds using ar elatively inexpensive,c ommercially available,e asy to handle reagent with simple manipulation is highly desired. TMSCF 3 ,n ow known as the Ruppert-Prakash reagent, has been the most widely used and versatile trifluoromethylation reagent for various substrates [2d,h,13] since its preparation by Ruppert et al [14] and application in nucleophilic trifluoromethylation by Prakash et al [15] Foralong time, TMSCF 3 was only considered atrifluoromethylation reagent (Scheme 1a,p ath a).…”
mentioning
confidence: 99%